A internet como espaço de atuação política para mulheres capoeiristas em tempos de isolamento - PENA, Luana de Nazaré Pinto (Universidade Federal do Pará, 2024)
Networked spaces have shaped new dynamics of sociability, enabling the intertwining of different historical-social contexts, a multiplicity of groups, organizations and subjects with different profiles of action and social and political mobilization, which have reached new heights from the contexts driven by the COVID-19 pandemic in 2020. It was in this scenario that capoerista paraense Sabrina Silva used Facebook lives to spread the female capoerista movement in Pará. In view of the above, this study aimed to analyze how the internet became a locus of political action for women capoeiristas during the pandemic in 2020, based on the case study of Sabrina Silva's Lives. To carry out the analysis, we adopted digital ethnography as a method, which is an adaptation of ethnographic analysis for the study of online cultures, aiming to explore and expand the possibilities through the constant use of digital networks, posting the material collected. With regard to the theoretical framework, we selected, among others, authors who work on issues related to capoeira, such as Nestor Capoeira (1999), Letícia Reis (2000) and Luiz Augusto Leal (2005); authors who discuss social movement relations today, such as Manuel Castells (2014) and Maria da Gloria Gohn (2011); authors who debate issues of gender, race and class, for example Anne McClintock (1995) and Kimberlé Crenshaw (2002); and theorists who discuss the digital ethnography , namely Beatriz Lins, Carolina Parreiras and Eliane Freitas (2020). As a result, it was found that social media was appropriated by women during a period when physical meetings were suspended, in order to spread a struggle so important to the construction of Brazilian culture, thus highlighting the power relations present in capoeira and its possibilities for expanding discussions on the subject and giving it more visibility.